Respiratory Impairment Predicts Response to IL-1 and IL-6 Blockade in COVID-19 Patients With Severe Pneumonia and Hyper-Inflammation - Della-Torre, Emanuel; Lanzillotta, Marco; Campochiaro, Corrado; Cavalli, Giulio; De Luca, Giacomo; Tomelleri, Alessandro; Boffini, Nicola; De Lorenzo, Rebecca; Ruggeri, Annalisa; Rovere-Querini, Patrizia; Castagna, Antonella; Landoni, Giovanni; et al. (Frontiers in Immunology, 2021)
Background. Restraining maladaptive inflammation is considered a rationale strategy to treat severe COVID-19 but available studies with selective inhibitors of pro-inflammatory cytokines have not provided unequivocal evidence of survival advantage. Late administration is commonly regarded as a major cause of treatment failure but the optimal timing for anti-cytokine therapy initiation in COVID-19 patients has never been clearly established. Objectives. To identify a window of therapeutic opportunity for maximizing the efficacy of interleukin (IL)-1 and IL-6 blockade in COVID-19. Methods. Survival at the longest available follow-up was assessed in severe hyper-inflamed COVID-19 patients treated with anakinra, tocilizumab, sarilumab, or standard of care, stratified according to respiratory impairment at the time of treatment initiation. Results. 107 patients treated with biologics and 103 contemporary patients treated with standard of care were studied. After a median of 106 days of follow-up (range 3-186), treatment with biologics was associated with a significantly higher survival rate compared to standard therapy when initiated in patients with a PaO2/FiO2 ≥ 100 mmHg (p < 0.001). Anakinra reduced mortality also in patients with PaO2/FiO2 < 100 mmHg (p = 0.04). Conclusions. IL-1 and IL-6 blocking therapies are more likely to provide survival advantage in hyper-inflamed COVID-19 patients when initiated before the establishment of severe respiratory failure.